An Analysis of Political Ethics from the Perspective of Muhammad Arkoun - Surianto, Annisa Pratiwi; Junaidi, Junaidi (Universitas Islam Negeri Sumatera Utara, 2024)
This study is grounded in the profound need to comprehend the role of Mohammed Arkoun, a postmodern/contemporary scholar, in revitalizing the potential of Islamic thought in the 21st century. The article underscores Arkoun's significance as an Islamic philosopher who successfully integrates the